[KCPR] Collection, 1971-1976 (1976)
[00:00:00] Jingle and information about KCPR's broadcasting [00:01:24] Jingle for ending broadcast with information about KCPR's broadcasting [00:03:09] KCPR Jingle - More Music [00:03:13] KCPR Jingle - Evolving/Changing [00:03:32] May 29 Request Day [00:04:03] "Bruce Queen" endorsement for 2000 watt broadcast [00:04:57] 2000 Watt sign-on advertisement in the style of Frankenstein/Dracula [00:05:56] Bluegrass style jingle [00:06:37] Air raid siren jingle for new stereo signal [00:07:22] "Abdul Kazudhess" commercial for KCPR auction to raise [00:09:04] "Rockin' Ralphie" commercial for stereo broadcast money for stereo conversion [00:09:35] Jingle [00:09:48] Larry Lafoett, Ron, Blair Helsing [mentioned], during the changeover to stereo broadcast, 1812 Overture played [00:13:35] Spot about the wonders of stereo with various examples of stereo sound: Louis Armstrong, bowling alley, jet airplane [00:15:35] Rick Tembull, Bat Masterson, Mike Ritatta, Dale Andrews [pitch wavers] [00:19:35] Sunday By Request advertisement [00:20:38] Country Music Lone Star Program with David Wayne spot [00:21:29] The Captain; Jim Allen; Mark Miller interview spot [00:22:39] KCPR Auction mob boss spot [00:24:36] Time Machine "Chief Running Chicken" spot for KCPR Disco Dance